ANALYSIS OF SAFETY MANAGEMENT PRACTICES AND QUALITY EDUCATION DELIVERY IN PUBLIC TERTIARY INSTITUTIONS IN IMO STATE, NIGERIA - Jude, opara (IJRDO - Journal of Business Management, 2018)
This study examined safety management practices as correlate of quality education delivery inpublic tertiary institutions in Imo State, Nigeria. Three (3) research questions and threehypotheses were formulated to guide the study. The methodology used the Ordinary LeastSquare (OLS) since it enabled the researcher to capture the essence of the work effectively inaddition to its high level of simplicity and global acceptability. The diagnostic tests such asnormality, serial correlation, heteroscedasticity and multicollinearity were all examined. Thepopulation of the study consists of all the lecturers in the four selected public tertiary institutionsin Imo State, Nigeria, and a sample of size two hundred and twelve (212) was employed in thisstudy. Research questions 1–2 were answered using Simple Pearson (r) correlation coefficientstatistic, while research question 3 was answered using multiple Pearson correlation coefficientstatistic. Hypotheses 1–2 were tested using simple linear regression statistic, while hypothesis 3was tested using multiple linear regression statistic at a p< 0.05 level of significance. Thefindings revealed the following: there is a high significant relationship between environmentalsafety practices and quality education delivery in public tertiary institutions in Imo State; there isa very high significant relationship between safety training and quality education delivery inpublic tertiary institutions in Imo State; there is a very significant multiple linear relationshipsamong environmental safety practices, safety training and quality education delivery in publictertiary institutions in Imo State. Based on the findings, the study recommended that: the schoolmanagement should make adequate provision of safety facilities that would enhance the safety ofthe staff and students in public tertiary institutions in Imo State; the school management shouldalso endeavour to ensure that the available facilities and social amenities are in good conditionthrough adequate maintenance to ensure the safety of the staff and students in public tertiaryinstitutions in Imo State, among others